2008
DOI: 10.1007/s12272-001-1162-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of citral on NO production by suppression of iNOS expression and NF-κB activation in RAW264.7 cells

Abstract: Citral is a major compound of lemongrass (Cymbopogon citratus L.) that has many pharmacological activities such as anti-fungal and anti-bacterial effects. In this study, we investigated the anti-inflammatory effect of citral and defined its mechanism of action in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. Citral (3-12 microg/mL) significantly inhibited LPS-induced nitric oxide (NO) production in a concentration-dependent manner (IC50: 6.5 microg/mL). Furthermore, it was found that citral effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 32 publications
2
58
1
2
Order By: Relevance
“…Some studies have been conducted with citral, the main volatile compound of the essential oil of Cymbopogon citratus (Cy) (Cheel et al, 2005;Lee et al, 2008), however little is known about the properties and mechanisms of action of the fixed compounds, namely polyphenols. Therefore, in the present study we analyzed their anti-inflammatory potential and evaluated some molecular targets of these extracts in LPS-stimulated Raw 264.7 cells.…”
Section: Evaluation Of the Anti-inflammatory Properties And Molecularmentioning
confidence: 99%
“…Some studies have been conducted with citral, the main volatile compound of the essential oil of Cymbopogon citratus (Cy) (Cheel et al, 2005;Lee et al, 2008), however little is known about the properties and mechanisms of action of the fixed compounds, namely polyphenols. Therefore, in the present study we analyzed their anti-inflammatory potential and evaluated some molecular targets of these extracts in LPS-stimulated Raw 264.7 cells.…”
Section: Evaluation Of the Anti-inflammatory Properties And Molecularmentioning
confidence: 99%
“…Our data suggest that citral may also suppress COX-2 promoter activity in a PPARγ-independent manner, since activation of PPARγ was similar with citral and carvacrol. Citral has been reported to suppress the expression of inducible nitric synthase (iNOS) gene by LPS, and suppress the DNA-binding activity of the NF-kB site of the iNOS gene (Lee et al, 2008). Moreover, it has been shown to activate several TRP thermosensitive channels with different affinities: that is TRPM8 (EC 50 = 33.5 μM) and TRPA1 (EC 50 = 200 μM) (Stotz et al, 2008) (Table 1) Inoue, H., Jiang, X., Katayama, T., Osada, S., Umesono, K. and Namura, S. (2003).…”
Section: Resultsmentioning
confidence: 99%
“…In this regards, Katsukawa et al (2010) identified CIT as a suppressor of COX-2 and an activator of peroxisome proliferator-activated receptors (PPAR) α and γ. Moreover, Lee et al (2008) showed that CIT inhibits NO generation through suppression of iNOS expression via inhibition of NF-κB activation.…”
Section: Resultsmentioning
confidence: 99%